Seroprevalence study for selected zoonotic vector-borne pathogens in sheep from endemic areas of Croatia - Barbic, Ljubo; Stevanovic, Vladimir; Mauric Maljkovic, Maja; Miletic, Gorana; Coric, Ivona; Savic, Vladimir; Masovic, Viktor; Bogdanic, Maja; Medic, Alan; Vilibic-Cavlek, Tatjana (Frontiers in Veterinary Science, 2025)
Surveillance is crucial in controlling and preventing vector-borne zoonotic diseases (VBDs). We analyzed the seroprevalence of selected vector-borne zoonotic pathogens in sheep from endemic areas and their role as possible sentinels for VBDs. A total of 300 sheep from seven farms at three micro-locations were tested for the presence of IgG antibodies against tick-borne encephalitis virus (TBEV), West Nile virus (WNV), Usutu virus (USUV), Borrelia burgdorferi s.l., and Crimean-Congo hemorrhagic fever virus (CCHFV) using ELISA with confirmation of borderline/positive results by VNT. Seropositivity for at least one pathogen was observed in 18.0% (54/300) of sheep. The highest seroprevalence was confirmed for TBEV (9.7%; 29/300), followed by WNV (3.0%; 9/300) and B. burgdorferi s.l. (2.7%; 8/300), while USUV and inconclusive flavivirus (TBEV/WNV/USUV) infections had the same seroprevalence of 1.3% (4/300). None of the serum samples tested positive for CCHFV. Geographic micro-location was a significant risk factor for USUV (p = 0.045), TBEV (p = 0.03), and B. burgdorferi s.l. (p = 0.015) infections, but not for WNV. The farm distance from the household (TBEV p < 0.001, B. burgdorferi s.l. p = 0.005) and sheep breed (TBEV p < 0.001, B. burgdorferi s.l. p < 0.001) were found as risk factors for seropositivity to tick-borne (TBEV, B. burgdorferi s.l.), but not to mosquito-borne diseases (WNV, USUV). Of the other risk factors, sheep shearing was statistically significant, with unshared sheep showing a higher probability of tick-borne diseases (p = 0.048). Sex, age, herd size, and the presence of clinical signs were not associated with the seroprevalence. Serologic evidence of VBDs suggests their sentinel potential for mapping micro-foci of zoonotic pathogens’ activity and identifying high-risk areas for public health. Further studies are needed to confirm this observation.